THE DEVELOPMENT OF QUANTITATIVE MODEL FOR EVALUATION OF BUSINESS PROCESS IMPROVEMENT WITH MULTI-OBJECTIVE - SARVIA (NIM 23406014), ELTY
Business process is a set of related activities carried out by an enterprise to deliver particular service to clients. In a competitive business there is a frequent need for enterprise to modify their design of business process to become more successful in the marketplace. By focusing on the optimization of business process improvement, enterprise can establish a solid competitive advantage by reducing cost, improving work performance, and enabling other adaptation for changing of business process. However, most of the current attemps for business process optimization is qualitative, which result is difficulties for detail analysis. This research developes a multi-objective optimization of business process design using quantitative analysis. The optimization variables to be chosen for this research were activities and it's starting times. The aim was to produced an improved business process design by minimizing two objectives that are cost and process duration. This methodology uses IDEF3 (Integrated Definition Methodology) method for capturing information flows among activities, and then formulated in a mathematical model. The solution is found by using modified NSGA-II (Non Dominated Sorting in Genetic Algorithm). The business process model was optimized by defining the model's optimization variables and objectives at early planning stage; current process performances are measured by getting process decomposition from the highest to the the lowest level; process improvements were identified with qualitative analysis if possible; then several preference alternatives were raised for each activities of business process design, afterwards the business process along with their preferences alternatives were mapped by using IDEF3 method. The next stage was formulating mathematical model by using variables and objectives which have been chosen; and the last stage of methodology was finding solution by modified NSGA-II to produce a satisfactory number of alternative arrangements of optimized business process. The proposed model in this research can be used in business process problems which has been decomposited untill the lowest level, so that the problems can be localized and the proposed alternatives structure relation for each activities are fixed. The proposed model in this research also can be used for business process which has more than two activities and each activities have several preference alternatives either they are serial, parallel, having bottleneck, but having no cycle.